A Rare Case of Ventricular Standstill and High-Grade AV Block in Patient with Thyrotoxicosis - Aryaputra, Achmad Bima; Bagaswoto, Hendry Purnasidha (The Indonesian Heart Association, 2025)
In “A Rare Case of Ventricular Standstill and High-Grade AV Block in Patient with Thyrotoxicosis” (Indonesian Journal of Cardiology, 43(4), 159-67. https://doi.org/10.30701/ijc.1299), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1299. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1299